Perancangan Iklan Layanan Masyarakat Tentang Bahaya Balap Liar Di Jalan Udayana - Miyarta yasa; Rasta maulana rahmanto; Sandi justitia putra (Universitas Bumigora, 2019)
Wild motor racing is an activity that is negative and full of danger both to themselves and others. Illegal racing activities occur because of negative associations among teenagers and a lack of attention from parents, families and their environmental communities. To overcome the possibility of unwanted things getting worse, socialization and direction is needed to teenagers or young children, through various means or can use various kinds of information media, one of which is public service announcements. The purpose of designing public service announcements about the dangers of illegal racing is to increase public awareness of orderly driving on the highway, educate the people of Mataram City and create a safe and comfortable atmosphere. Public Service Announcements to be designed using the analysis method 5W + 1H. The public service advertisement that the writer designed was aimed at the city of Mataram, especially on Udayana Street with the main priority target audience being the youth and the general public. The design is themed about the dangers of wild racing using print media in the form of billboards. It is expected that the existence of Public Service Advertisements through billboards can give awareness to illegal racers not to carry out illegal racing activities, provide references to similar studies to make designs that can really hit the hearts of the target audience and the government is expected to be able to take more real action in dealing with the dangers of wild motor racing.